Residual charge effects on partial discharges' response to varying sub‐kHz voltage frequencies - Cuthbert Nyamupangedengu; Tapiwa Venge (High Voltage, 2023)
Abstract Partial discharges (PD) are the ‘cancer’ of electrical insulation. Insulation design and mitigation of PD‐induced degradation should be based on good knowledge of PD phenomena. In that regard, a significant body of knowledge has been built up from concerted research across the world in past decades and on various aspects of PD phenomena under various conditions. However, the work is far from being complete as new challenges arise. One such challenge is that electric power equipment insulation is becoming more exposed to non‐power frequency voltages. Examples are the proliferation of invertor‐based grid‐tied renewable energy sources and other technologies such as high‐frequency power electronic transformers. Questions that are driving continued research in this regard include the reasons for lack of consensus on the findings on how PD characteristics respond to variations in the voltage frequency. This paper presents results of how residual charge influences PD characteristics' response to voltage frequency changes from 1 to 200 Hz. The study approach is implementing the extended 3‐capacitor PD model in MATLAB® Simulink® and validating the findings using the relevant experimental results that are available in literature. The PD type studied is that of an air cavity encapsulated in a polyethylene dielectric. Highlights of the findings are that the extent of the influence of residual charge on PD characteristics depends on the relative magnitude of the residual charge as well as the voltage frequency. The relationships however exhibit non‐monotonous trends. Such results further confirm similar findings and conclusions by other researchers and could be signalling the establishment of a more solid knowledge base for design of insulations that operate at non‐power frequencies.